Sintesis dan Karakterisasi Nanokristal Selulosa Berbasis Biomassa Serat Sawit sebagai Material Isolasi Panas - Ina Ristian; Muhammad Rizki Kurniawan; Renny Septiani Mokodongan; Siti Nur Fauzia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to synthesize cellulose nanocrystals (CNC) from oil palm biomass and to characterize their properties. The method involved cellulose isolation through delignification using alkaline salts, followed by CNC synthesis via acid hydrolysis, and characterization using Scanning Electron Microscopy (SEM) and Particle Size Analyzer (PSA). The PSA analysis showed that CNC had an average diameter of 30 nm, with a small fraction ranging from 90 to 100 nm and another fraction reaching 10 nm. Morphological analysis by SEM revealed that CNC exhibited a rough surface. In conclusion, the obtained CNC has potential applications as a functional material in various fields, particularly in the automotive sector as a thermal insulation material. Keywords: Biomass, Cellulose, Insulation, Nanocrystal, Oil Palm Fiber